Comparing Lab-Work Learning Assisted with Vee Diagram and Lecturing-Demonstration in Improving Students Learning Motivation and Outcomes on Buffer Solution Topic - Ardian Trio Wicaksono; Subandi Subandi; Siti Marfu’ah (Pascasarjana Universitas Negeri Malang (UM), 2018)
Abstract: This study aims at confirming and proving the comparison of two learning method, lecturing-demonstration and lab-work assisted with Vee Diagram, in buffer solution topic to students’ learning motivation and learning outcomes. This study is a quasi-experiment with balanced control group design. The subject of this study was XI Graders of IPA 1 and IPA 3. The results of this study indicate that lab-work learning assisted with Vee Diagram could motivate more the students as well as generating students high-order thinking skills than lecturing-demonstration learning method.Key Words: lecturing-demonstration, lab-work assisted with Vee Diagram, motivation, learning outcomes, buffer solution topic Abstrak: Tujuan penelitian ini adalah untuk mengetahui perbandingan keefektifan pembelajaran larutan penyangga menggunakan ceramah demonstrasi dan praktikum berbantuan Diagram Vee terhadap motivasi dan hasil belajar siswa. Penelitian ini merupakan quasi experiment dengan balanced control group design. Subjek penelitian adalah siswa kelas XI IPA 1 dan IPA 3. Hasil penelitian ini menunjukkan bahwa pembelajaran larutan penyangga menggunakan praktikum berbantuan Diagram Vee lebih memotivasi siswa dibandingkan dengan pembelajaran ceramah demonstrasi, dan praktikum berbantuan diagram Vee menghasilkan kemampuan berpikir tingkat tinggi yang lebih baik. Kata-kata kunci: ceramah demonstrasi, praktikum berbantuan diagram Vee, motivasi, hasil belajar, topik larutan penyangga